2014
DOI: 10.2478/s11532-014-0541-3
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of amoxicillin from bacterial cellulose membranes

Abstract: Bacterial cellulose (BC), a natural polymer with unique physical and mechanical properties, has several applications in the biomedical field, including drug loading and controlled drug delivery. For this study, a Box-Behnken experimental design was employed as a statistical tool to optimize the release of a model drug, amoxicillin, from BC membranes. Independent variables studied were the concentration of the drug (X1), the concentration of glycerol (X2) and the concentration of a permeation enhancer (X3). Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…an exopolysaccharide produced by some non-pathogenic bacteria, namely the acetic acid bacteria of the genus Komagataeibacter (formerly classified as Gluconacetobacter) [17,18], is gaining increasing attention in the biomedical realm [19][20][21], particularly as a wound-dressing material [19,22,23]. Hence, the current study was inspired not only by the biocompatibility, high water-retention capacity, nanostructured porous network and good in vivo skin compatibility of BNC [20,24], but also by the fact that this exopolysaccharide can be directly produced in the form of membranes or films with customizable size and shape, and can house an array of active molecules (e.g., lidocaine [25,26], diclofenac [27,28], amoxicillin [29] and levofloxacin [30]) and macromolecules (e.g., poly([2-(methacryloyloxy)ethyl]trimethylammonium chloride) [31] and vitamin B-based ionic liquids [32]) that confer new functionalities to the ensuing materials. Although (i) HA has already been added to the culture media during BNC biosynthesis, to obtain BNC/HA membranes with no specific application [33], and (ii) the combination between BNC and DCF has already been studied for transdermal delivery [27], the coalition of BNC with HA and DCF has not yet been studied, at least to the best of our knowledge, for the potential treatment of aphthous stomatitis.…”
Section: Introductionmentioning
confidence: 99%
“…an exopolysaccharide produced by some non-pathogenic bacteria, namely the acetic acid bacteria of the genus Komagataeibacter (formerly classified as Gluconacetobacter) [17,18], is gaining increasing attention in the biomedical realm [19][20][21], particularly as a wound-dressing material [19,22,23]. Hence, the current study was inspired not only by the biocompatibility, high water-retention capacity, nanostructured porous network and good in vivo skin compatibility of BNC [20,24], but also by the fact that this exopolysaccharide can be directly produced in the form of membranes or films with customizable size and shape, and can house an array of active molecules (e.g., lidocaine [25,26], diclofenac [27,28], amoxicillin [29] and levofloxacin [30]) and macromolecules (e.g., poly([2-(methacryloyloxy)ethyl]trimethylammonium chloride) [31] and vitamin B-based ionic liquids [32]) that confer new functionalities to the ensuing materials. Although (i) HA has already been added to the culture media during BNC biosynthesis, to obtain BNC/HA membranes with no specific application [33], and (ii) the combination between BNC and DCF has already been studied for transdermal delivery [27], the coalition of BNC with HA and DCF has not yet been studied, at least to the best of our knowledge, for the potential treatment of aphthous stomatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that pure BNC membranes can be successfully loaded with multiple active pharmaceutical ingredients (APIs) (or other bioactive molecules) with different structures, solubility and hydrophilicity. For instance, neat BNC membranes have already been combined with drugs and other bioactive compounds, such as lidocaine [22,23], ibuprofen [23], caffeine [24], diclofenac [25] and amoxicillin [26] in their most common forms or formulated as ionic liquids [27,28] for cutaneous drug delivery. There are also examples of BNC-based nanocomposites being used for the cutaneous delivery of diclofenac [29] and BNC-based hybrid films for the cutaneous delivery of levofloxacin [30].…”
Section: Introductionmentioning
confidence: 99%
“…In study using the Box-Behnken statistical design to study the release of amoxicillin (AMX) from the BC, BC / glycerol and BC / hexadecyltrimethylammonium bromide enhancer showed that amoxicillin concentration had a greater influence on drug release and a significant contribution was also observed for the linear and quadratic terms of the glycerol concentration, the linear concentration of potentiator, and the interaction between the concentration of glycerol and concentration of the enhancer. These results show that independent variables affevct the release of AMX from BC membranes (23).…”
Section: Introductionmentioning
confidence: 56%